Factors Associated with the Incidence of Diarrhea in the Regional Technical Implementation Unit (UPTD) of the Community Health Center - Alfian Mas'ud (Newinera Publisher, 2021)
In general, the problem of diarrhea disease is one of the environmental-based diseases which is still the biggest health problem in Indonesia due to poor basic sanitation conditions, the physical environment and the low behavior of the community to live clean and healthy, and there are still many factors that cause the emergence of diarrhea disease. This research method is descriptive analytic with cross sectional design with a research sample of 112 people. Data analysis used univariate analysis and bivariate analysis with Chi square statistical tests. The results of this study indicate the relationship between predisposing factors such as education with a value of p = 0.000 (p <0.05), work with a value of p = 0.013 (p <0.05), income with a value of p = 0.024 (p <0.05) and knowledge with a value p = 0.13 (p> 0.05) and attitude p = 0.47 (p> 0.05). The conclusion in this research is that there is a relationship such as education, work and income, there is no relationship between knowledge and attitude with the incidence of diarrhea. It is recommended that mothers under five should always adopt clean and healthy living habits and provide nutritious food to avoid infectious diseases, especially diarrhea